The influence magnesium deficit on mental and motor human efficiency - Terelak, Jan Felicjan; Walasek, L.; Ligocki, P.; Tarnowski, Andrzej (Studia Psychologica: Theoria et praxis, 2003)
The aim of the study was to evaluate magnesium condition in selected professional groups which are under the influence of stress factors (army pilots) and also the efficiency of magnesium supplementation on physical efficiency and subjective ailment (sickness) which might be caused by deficit of magnesium. The study was performed on 37 people, aged 24 – 50 (average 37.4). Two groups of subjects were selected from a random control trial, 20 in the examined group and 17 in controlled. The intravenous supplementation of magnesium by intravenous infusion was applied in the first group and the second received intravenous placebo. After obtaining required results a questionnaire was used to check occurring subjective symptoms and a psychological test was made (simple reaction time, Bourdon’s attention test, arithmetic test). The results of the study showed influence of magnesium supplementation on attention processes gained from Bourdon’s test. There were no statistically significant changes in the other tests.